Proposed new interior design of Hotel De Art at No. 1, Jalan Tengku Ampuan Zabedah B 9/B, Section 9, Shah Alam, Selangor for Hotel De Art / Nur Nadzirah Mahat - Mahat, Nur Nadzirah (2012)
In this project, it will bring up the study or research on boutique hotel design for Hotel De Art. All the information is gain throughout many methods such as interview, case study, observation, internet and books to produce a good design. All of this information will be compiled and used as a guideline in design process. Boutique hotel is style, distinction, warmth, and intimacy are key words in the architecture and design of boutique hotels, which seem to attract a niche of customers looking for a special and differentiated property able to fulfil their individual needs. This project title is Proposed New Interior Design of Boutique Hotel at no. 1, Jalan Tengku Ampuan Zabedah B, 9/B, Section 9, 40000 Shah Alam , Selangor . The aim of design is to design a boutique hotel includes with a good and comfortable accommodations to complete guest needs and comfort. With the chosen concept; "legend, bring back the memorial of Malaysian Legendary Artist: P.Ramlee", this project will be bring the nostalgia of P.Ramlee and gave a great impression from P.Ramlee fans locally and internationally.